Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a ) Ta có : 4(x - 5) - 3(x + 7) = -19
<=> 4x - 20 - 3x - 21 = -19
=> x - 41 = -19
=> x = -19 + 41
=> x = 22
b) Ta có " 7(x - 3) - 5(3 - x) = 11x - 5
<=> 7x - 21 - 15 + 5x = 11x - 5
<=> 12x - 36 = 11x - 5
=> 12x - 11x = -5 + 36
=> x = 31
\(a.\Leftrightarrow2|x-6|-|x-6|-2=0\)
\(\Leftrightarrow|x-6|-2=0\)
\(\Leftrightarrow|x-6|=2\)
\(+x-6=2\)
\(\Leftrightarrow x=8\)
\(+x-6=-2\)
\(\Leftrightarrow x=4\)
v...
\(b.\Leftrightarrow-4\left(5-x\right)-7\left(5-x\right)+10\left(5-x\right)=-3\)
\(\Leftrightarrow\left(5-x\right)\left(10-4-7\right)=-3\)
\(\Leftrightarrow-1.\left(5-x\right)=-3\)
\(\Leftrightarrow5-x=3\)
\(\Leftrightarrow x=2\)
v...
1. A = (-2)(-3) - 5.|-5| + 125.\(\left(-\dfrac{1}{5}\right)^2\)
= 6 - 25 + 125.\(\dfrac{1}{25}\)
= -19 + 5
= -14
@Shine Anna
1,\(\frac{2}{9}.\left(x-\frac{9}{4}\right)+\frac{1}{2}=\frac{3}{7}.\left(7-\frac{1}{6}\right)+\frac{1}{3}\)
\(\frac{2}{9}.\left(x-\frac{9}{4}\right)+\frac{1}{2}=\frac{3}{7}.\frac{41}{6}+\frac{1}{3}\)
\(\frac{2}{9}.\left(x-\frac{9}{4}\right)+\frac{1}{2}=\frac{41}{14}+\frac{1}{3}\)
\(\frac{2}{9}.\left(x-\frac{9}{4}\right)+\frac{1}{2}=\frac{137}{42}\)
\(\frac{2}{9}.\left(x-\frac{9}{4}\right)=\frac{137}{42}-\frac{1}{2}\)
\(\frac{2}{9}.\left(x-\frac{9}{4}\right)=\frac{58}{21}\)
\(\left(x-\frac{9}{4}\right)=\frac{5}{2}:\frac{2}{9}\)
\(\left(x-\frac{9}{4}\right)=\frac{45}{4}\)
\(x=\frac{45}{4}+\frac{9}{4}\)
\(x=\frac{27}{2}\)
Bài 1:
d)
= \(\frac{-5}{9}\left(\frac{6}{13}+\frac{7}{13}\right)+\frac{5}{23}.\frac{7}{9}\)
= \(\frac{-5}{9}.1+\frac{35}{207}\)
= \(\frac{-80}{207}\)
Bài 2:
a) 20%x + 0,4x = 4,5
x( 20% + 0,4 ) = 4,5
x. 0,6 = 4,5
x = 4,5 : 0,6
x = 7,5
\( 19 { \left(2+3+4-5+6-7 \right) }^{ { 2 }^{ 2 } } -9 \left( 7x-2 \right) = 0 \)
\(\Rightarrow19\cdot\left(2+3+4+5+6-7\right)^4-9\left(7x-2\right)=0\)
\(\Rightarrow19\cdot\left(5+9-1\right)^4-9\left(7x-2\right)=0\)
\(\Rightarrow19\cdot13^4-9\left(7x-2\right)=0\)
\(\Rightarrow19\cdot28561-9\left(7x-2\right)=0\)
\(\Rightarrow542659-9\left(7x-2\right)=0\)
\(\Rightarrow9\left(7x-2\right)=542659\)
\(\Rightarrow7x-2=542659:9\)
\(\Rightarrow7x=\dfrac{542659}{9}+2\)
\(\Rightarrow7x=\dfrac{542677}{9}\)
\(\Rightarrow x=\dfrac{542677}{9}:7\)
\(\Rightarrow x=\dfrac{542677}{63}\)